2019
DOI: 10.1186/s13019-019-1026-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative platelet count, preoperative hemoglobin concentration and deep hypothermic circulatory arrest duration are risk factors for acute kidney injury after pulmonary endarterectomy: a retrospective cohort study

Abstract: BackgroundAcute kidney injury (AKI) is a major postoperative morbidity of patients undergoing cardiac surgery and has a negative effect on prognosis. The kidney outcomes after pulmonary endarterectomy (PEA) have not yet been reported; However, several perioperative characteristics of PEA may induce postoperative AKI. The objective of our study was to identify the incidence and risk factors for postoperative AKI and its association with short-term outcomes.MethodsThis was a single-center, retrospective, observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Zhang et al (51) published the first report on a complication study of 123 patients diagnosed with chronic thromboembolic pulmonary hypertension (CTEPH) who underwent pulmonary endarterectomy (PEA). Their data suggested that the incidence of postoperative AKI was 45% (Table 2); that preoperative platelet count, hemoglobin concentration, and duration of deep hypothermic circulation stagnation were independent factors associated with AKI; and that renal protection strategies should be prioritized in the perioperative management of such procedures (51). However, some unknown confounding factors (such as perioperative nephrotoxic drug use) were not explicitly excluded in this study, and there are not enough other relevant studies due to the low incidence of CTEPH, resulting in some limitations of the findings.…”
Section: Special Surgical Interventionsmentioning
confidence: 99%
“…Zhang et al (51) published the first report on a complication study of 123 patients diagnosed with chronic thromboembolic pulmonary hypertension (CTEPH) who underwent pulmonary endarterectomy (PEA). Their data suggested that the incidence of postoperative AKI was 45% (Table 2); that preoperative platelet count, hemoglobin concentration, and duration of deep hypothermic circulation stagnation were independent factors associated with AKI; and that renal protection strategies should be prioritized in the perioperative management of such procedures (51). However, some unknown confounding factors (such as perioperative nephrotoxic drug use) were not explicitly excluded in this study, and there are not enough other relevant studies due to the low incidence of CTEPH, resulting in some limitations of the findings.…”
Section: Special Surgical Interventionsmentioning
confidence: 99%
“…We read with great interest the recent article by Zhang et al [1] determining the risk factors of acute kidney injury (AKI) after pulmonary endarterectomy with cardiopulmonary bypass (CPB). By univariate and multivariate logistic regression analyses, they showed that preoperative platelet count and hemoglobin level, and deep hypothermic circulatory arrest time were the independent predictors of postoperative AKI.…”
Section: To the Editormentioning
confidence: 99%
“…The reported incidences of AKI in cardiovascular surgical patients at Fuwai Hospital vary from 7.5% to 77.6%, with the dialysis dependence incidence between 7.9% and 58.9%. [92][93][94] The spectrum of postoperative pulmonary complications (PPCs) in cardiovascular surgical patients ranges from transient hypoxemia, acute respiratory distress syndrome (ARDS), pulmonary infection, atelectasis, pulmonary edema, etc. For example, the reported incidence of postoperative pulmonary infection and atelectasis at Fuwai Hospital was 5.8% and 1.7%, respectively.…”
Section: ⅱ Morbiditiesmentioning
confidence: 99%